Probing the effect of the Pt–Ni–Pt(111) bimetallic surface electronic structures on the ammonia decomposition reaction. Issue 2 (12th December 2016) - Zhong, Jian-Qiang; Zhou, Xiong; Yuan, Kaidi; Wright, Christopher A.; Tadich, Anton; Qi, Dongchen; Li, He Xing; Wu, Kai; Xu, Guo Qin; Chen, Wei
Abstract : A detailed elementary catalytic decomposition of ammonia on Pt–Ni–Pt(111) was observed by using in situ near ambient pressure X-ray photoelectron spectroscopy. Abstract : We report a detailed investigation of elementary catalytic decomposition of ammonia on the Pt–Ni–Pt(111) bimetallic surface using in situ near ambient pressure X-ray photoelectron spectroscopy. Under the near ambient pressure (0.6 mbar) reaction conditions, a different dehydrogenation pathway with a reduced activation energy barrier for recombinative nitrogen desorption on the Pt–Ni–Pt(111) bimetallic surface is observed. The unique surface catalytic activity is correlated with the downward shift of the Pt 5d band states induced by the Ni subsurface atoms via charge redistribution of the topmost Pt layer. Our results provide a practical understanding of the unique chemistry of bimetallic catalysts for facile ammonia decomposition under realistic reaction conditions.